Evaluating the Moral Framing of Disaffiliation: Sociological and Pastoral Perspectives on the Rise of the “Nones” - Brett C. Hoover (Religions, 2021)
The wave of religious disaffiliation that began in the 1990s in the United States has gone from a concern of pastoral leaders to perhaps the concern of pastoral leaders. This article examines a moral framing of religious disaffiliation—where disaffiliation is seen as a symptom of larger moral struggles in society. After a review of contemporary sociological research on the phenomenon of disaffiliation, its roots and causes, the article explores the thinking of the influential Catholic bishop and media entrepreneur Robert Barron as an example of the moral framing of religious disaffiliation. Barron operates as a “moral entrepreneur” in today’s media-rich context, working to persuade Catholics to eschew certain strains of secular and liberal Catholic thinking in order to embrace traditional Catholicism as part of a moral struggle for the soul of U.S. society. Sociological theory on moral entrepreneurship and moral regulation helps make sense of his position. In the end, however, the causes and processes revealed in sociological research on disaffiliation reveal the moral framing as an inadequate construct for making sense of the actual phenomenon. I conclude by recommending a “historical-pastoral” framing of disaffiliation instead.